Eradication of phosphatide - esters using biomaterial “ Conjugates like liposomes - Saadi, Sami; Mohd Ghazali, Hasanah; Saari, Nazamid; Ariffin, Abdul Azis; Mohammed, Abdulkarim Sabo; Anwar, Farooq; Nacer, Nor Elhouda (Elsevier, 2023)
The attempt of this review article is rewarded in forming copolymer vesicles with amphiphilic properties capable in detoxifying cellular impurities such as phosphatide and sulfatide ester groups. The obtained copolymer conjugates is aimed to exhibit desirable levels of hydrophylicity lipophilicity balances HLB, shear stiffness, surface tension, and slow release to bioactives. The designed system in turn is capable in carrying in advanced bioactives for depleting most of allergic, transgenic and mutagenic growth factors. The molecular labeling using radioactive tracing elements based fluorescent materials is the common chemical enhancement used in tracing the bioavailabilities of those vesicle structures, their transmissions and biodegradibilties. Conjugated effects of peptides and lipids are helpful in determining the ultrastructural dimensions of these vesicles eventually leading to appropriate control of the loading or coating materials necessary for efficient therapeutic targets, duration releases and stabilities.